INVESTIGATES THE ROLE OF COGNITIVE AND EMOTIONAL SCHEMAS IN STRESS - Sardarzadeh, Soorena (Psychological Prospects Journal, 2019)
The present study investigates the role of cognitive and emotional schemas in explaining stress. Stress is among the most prevalent mental and psychological problems that, if acute and continuous, can lead to depression and anxiety disorders that, in turn, will result in excessive use of health care services and excessive dysfunction in individuals. Based on the schematic viewpoint, the mental damage/harm caused by the formation and stability of cognitive schemas and emotional schemas, and the patterns of thinking and habitual excitement, which are very general and inclusive, identifies the type of vulnerability. Methodology: The present study is a post-event research (causal-comparative). To this end, three questionnaires of DASS questionnaire, cognitive schema questionnaire and emotional schema questionnaire were given to them simultaneously. Then, the subjects with high scores in stress, which were obtained from the questionnaire, were selected and divided into three groups of stress. The obtained data were analyzed. After calculating the descriptive statistics of the studied variables, the data of the research were analyzed using the statistic methods of Multivariate analysis of variance (MANOVA), ANOVA and Tukey’s method.Сonclusion: The findings show that people with high levels of stress have guilt and uncontrollability schemas that can be due to the impact of individuals’ cognitive schemas in analyzing and accepting various situations in life. Individuals with high levels of stress received high scores in Unrelenting Standards/Hypercriticalness cognitive schemas were observed.
Keywords: stress; emotional schema; cognitive schema; DASS; Early Maladaptive Schema